Experience of the use of liraglutide (Victoza) in women with type 2 diabetes mellitus and obesity - Vladimir Ivanovich Kudinov; Natalya Vladimirovna Zolotareva; Maria Sergeeva Nichitenko (Сахарный диабет)
Aim. To study efficacy of treatment with liraglutide in women with type 2 diabetes (T2D) and obesity. Materials and methods. A group of 12 women aged 52-58 yr with T2D duration of 3-5 years, BMI 32-35 kg/m2, abnormally high C-peptide level,and НbА1с 7.5-8.5% were treated with 1500-2000 mg metformin/day and sulfonylureas at 50% of the maximum dose. Liraglutide was given insteadof sulfonylureas by a standard method (0.6 U/day for 1 week subcutaneously and 1.2 U/day thereafter). The total duration of therapy was 3 months.We analysed blood glucose level before and 2 hr after meals, НbА1с, lipidogram, C-peptide, HOMA index, BMI, waist circumference, percent of totalfat in the body, frequency of hypoglycemia, and side effects (nausea). Results. All patients achieved target values of НbА1с and a significant decrease in blood glucose before and after meals, body weight, total fat content,BMI, HOMA, systolic blood pressure; HDL cholesterol increased while LDL decreased. No case of hypoglycemia was documented. All the patientshad mild nausea of short duration (2-3 days). Conclusion. The use of liraglutide (Victoza) in women with T2D and obesity improve carbohydrate metabolism and insulin resistance without seriousside effects.